The Mediating Effect of Training Perspective on the Relationship Between Competency Potential and Career Progression of Technical Vocational Trainers - Tulo, Amparo A.; Gempes, Gloria P. (International Journal of Management Excellence (ISSN: 2292-1648), 2016)
Abstract- The purpose of the study was to determine if the training perspective on trainers’ methodology had a significant mediating effect on the relationship between competency potential and career progression of the technical vocational trainers in Davao Region, Philippines. The design used was non-experimental quantitative research utilizing correlation technique. Descriptive statistics, pearson r, regression, mediation through sobel test and medgraph were the tools employed to attain the objectives of the study. The 407 respondents were found to show very high levels of competency potential, training perspective and career progression. It was found out that the three variables were significantly related. However, the result failed to achieve full mediation of training perspective on the relationship between the correlated variables. This implies that training perspective only mediated partially the relationship between competency potential and career progression. The result signifies that direct effect on career progression maybe due to the combination of competency potential and other variables not covered in the study.